Values of Government Public Relations for a Rocky Road to Participatory Democracy: Testing Public Engagement, Empowerment, and Serenity Hypotheses in Public Sector Communication - Myoung-Gi Chon (Coordinamento SIBA, 2020)
Voluntary citizen attention and actions are key to successful public-sector communication. We investigated the conditions which increase such attention and actions using the situational theory of problem solving (STOPS) and government-citizen relationships (GCRs). Using three national issues consisting of an environmental issue, a social issue, and a political issue from South Korea (N=275), this study examined three hypotheses regarding public engagement effect (the effect of GCRs on political conversations on national issues), government empowerment effect (the effects of GCRs and issue-specific trust toward government on constraint recognition), and public serenity effect (the effect of issue-specific trust on problem recognition and involvement recognition). We found significant public engagement and government empowerment effects and partially significant public serenity effect. The results of the public serenity investigation found that issue-specific trust toward government was significant with problem recognition but insignificant with involvement recognition. Consequently, the findings illustrate strategic values in government-citizen relationships on public engagement, empowerment, and serenity to enable participatory democracy.